The Influence of Artificial Intelligence Identity Threat on Employee Well-Being: The Mediating Roles of Cognitive Job Insecurity and AI Opportunity Perception at Manyar Medical Center Hospital - Rayhan Muhammad Basyarahil; Rian Andriani; Kahar Mulyani (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The development of Artificial Intelligence (AI) in the healthcare sector has brought significant changes to work systems and the psychological dynamics of healthcare professionals. On one hand, AI enhances services efficiency and accuracy, on the other, it raises concerns about human roles being replaced by technology. This condition potentially creates AI-induced identity threats that affect employee well-being. This study aims to analyze the effect of AI identity threat on employee well-being, with cognitive job insecurity and AI opportunity perception as mediating variables, at Manyar Medical Center Hospital. This research employed a quantitative method using a survey approach with 200 respondents through convenience sampling. Data were analyzed using Pearson correlation, linear regression, and Sobel mediation test. The results show that AI identity threat has a positive and significant effect on cognitive job insecurity and a negative and significant effect on AI opportunity perception. The relationship between AI identity threat and employee well-being was also found to be significantly negative. Both mediating variables partially mediate the relationship between AI identity threat and employee well-being, with a total indirect effect of 0,3948 (Z1=-3.182, p=0.0015 (M1); Z2=-6.531, p<0.001 (M2)). These findings confirm that employee well-being in the digital era is influenced not only by organizational factors but also by how individuals cognitively appraise the threats and opportunities posed by AI. The results highlight the importance of adaptive training, transparent organizational communication, and active employee involvement in technology implementation.